Education, market rigidities and growth - Philippe Aghion; Philippe Askenazy; Renaud Bourlès; Gilbert Cette; Nicolas Dromel (Institute for the Study of Labor (IZA), 2007)
This note investigates the effects of the education level, product market rigidities and employment protection legislation on growth. It exploits macro-panel data for OECD countries. For countries close to the technological frontier, education and rigidities are significantly related to TFP growth. The contribution of the interaction between product market regulation and labour market rigidity seems particularly substantial.
Keywords: O47; 330; Productivity; growth; regulations; market rigidities; education; Produktivität; Wirtschaftswachstum; Bildungsniveau; Unvollkommener Markt; Unvollkommener Wettbewerb; Kündigungsschutz; OECD-Staaten